2021
DOI: 10.1111/pbi.13549
|View full text |Cite
|
Sign up to set email alerts
|

High‐spatiotemporal‐resolution transcriptomes provide insights into fruit development and ripening in Citrus sinensis

Abstract: Citrus fruit has a unique structure with soft leathery peel and pulp containing vascular bundles and several segments with many juice sacs. The function and morphology of each fruit tissue are different. Therefore, analysis at the organ-wide or mixed-tissue level inevitably obscures many tissue-specific phenomena. High-throughput RNA sequencing was used to profile Citrus sinensis fruit development based on four fruit tissue types and six development stages from young fruits to ripe fruits. Using a coexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 94 publications
(132 reference statements)
2
38
0
Order By: Relevance
“…In the present study, the SUT gene (Aco000269) expression level showing a positive correlation with Suc content suggested that it was involved in apoplast unloading of Suc, whereas the SUT gene (Aco004135) expression level displaying a negative correlation with Suc content suggested that it was involved in Suc efflux from the vacuole membrane to the cytoplasm. Furthermore, the positive correlation between the SWEET gene (Aco016508) expression level and Suc content in this study showed that it might mediate Suc release into the apoplast and contribute to Suc accumulation in pineapple fruit based on a study in Citrus (Feng et al, 2021). The expression levels of the other three SWEET genes were negatively correlated with Suc content, which was consistent with previous studies (Guo et al, 2018).…”
Section: Reasons For Sucrose Accumulation During Pineapple Fruit Deve...supporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the SUT gene (Aco000269) expression level showing a positive correlation with Suc content suggested that it was involved in apoplast unloading of Suc, whereas the SUT gene (Aco004135) expression level displaying a negative correlation with Suc content suggested that it was involved in Suc efflux from the vacuole membrane to the cytoplasm. Furthermore, the positive correlation between the SWEET gene (Aco016508) expression level and Suc content in this study showed that it might mediate Suc release into the apoplast and contribute to Suc accumulation in pineapple fruit based on a study in Citrus (Feng et al, 2021). The expression levels of the other three SWEET genes were negatively correlated with Suc content, which was consistent with previous studies (Guo et al, 2018).…”
Section: Reasons For Sucrose Accumulation During Pineapple Fruit Deve...supporting
confidence: 91%
“…Citrate degradation by the GABA pathway in the cytosol is also a key player in fruit acidity ( Batista-Silva et al, 2018 ). GADs catalyze the decarboxylation of glutamate to GABA and are related to citrate accumulation, and the higher expression of GAD genes contribute to the decrease in fruit acidity at the late stage of development ( Liu et al, 2014 ; Feng et al, 2021 ). Low-acid cultivars exhibited citrate degradation attributed to the upregulation of GAD gene expression in peach ( Zheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We collected the expression profiles of C. sinensis (‘Fengjie 72-1′) albedo, epicarp, juice sac, and segment membrane from six fruit development stages, including 50 days after flowering (the second physiological fruit-falling period); 80, 120, and 155 days after flowering (the expansion period); 180 days after flowering (the coloring period), and 220 days after flowering (the full-ripening period) ( Feng et al, 2021 ). The average expression of all CsCHI genes was the highest in the 50 DAF stage, then decreased rapidly, and increased slightly in the 155 DAF stage ( Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…RNA-seq data for C. sinensis were obtained from the NCBI GEO DataSets under accession numbers PRJNA689213 and PRJNA517400 ( Feng et al, 2021 ; Huang et al, 2021 ). The transcriptome data of pulp and peel contained two types of sweet oranges (Valencia orange and common sweet orange), involving six varieties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation